Implementation of Character Education Management through Positive Habituation Activities - Muhammad Iqbal (Edumaspul: Jurnal Pendidikan, 2023)
Education has a very important role in the fulfillment of competitive human resources in the development of science and technology as well as substantial aspects, namely spiritual in order to be able to produce quality products. To avoid the rampant degradation of character, it is necessary to implement character education management in educational institutions. The purpose of this study was to determine the implementation of character education management through positive habituation activities at the MTs Laboratory of UINSU. This research uses qualitative methods. Qualitative research is research that presents data with a description. Data collection techniques are carried out by observation methods. This type of research is field research. Data analysis consists of three components, namely data reduction, data presentation and drawing conclusions. Based on the results of research, the implementation of character education management is integrated in school activities, namely habituation activities. Character education management activities are carried out in order to achieve the vision and mission of the school.